PELESTARIAN DAN PENGELOLAAN GEREJA BLENDUK SEMARANG - Irfanuddin Wahid Marzuki (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2011)
Dome church is the landmark of the old town in Semarang. Established in 1753, the building is still in a good shape now and even is used for Christians. The preservation and management program have been running very well. However, some matters are still not coherence with the Act No. 11 of 2001 concerning Cultural Resources.